Estructura y cinemátIca de los pliegues y cabalgamientos de Belchite-Sierra de Arcos (Cordillera Ibérica) - Casas Sainz, A.M.; Cortés Gracia, A.L. (Cuadernos de Geología Ibérica, 1999)
The northem margin of the iberian Chain at the Belchite-Sierra de Arcos region shows a set of folds and thrusts trending E-W and NW-SE. These structures were originated during the Tertiary by a N-S fo NNE-SSW regional shortening. Both orientation of folás and faults in the Variscan basement and regional detachment Ievels control tbe development of structures in the sedimentary cover. The Belchite anticline is located aboye a basement anticline which constitutes the NE margin of the Azuara Basin, a wide syncline or synclinorium of compressional origin. Main folds and thrusts extending in this area between the Siena de Arcos, at the northern margin, and the Montalbán Palaeozoic anticline, at the south, result either from the positive inversion during the Tertiary of Mesozoic extensional faults active during the Early Cretaceous, or correspond to thrusts nucleated on basement extensional steps created by these fau lts.
Keywords: Iberian Chain; folds; thrusts; extensional faults; tectonic inversIon